Cryptanalysis and improvement of blind signcryption scheme based on elliptic curve. Issue 8 (1st April 2019) - Bashir, Malik Zia Ullah; Ali, R.
Abstract : Blind signcryption schemes are the extension of signcryption schemes. They are used to protect the privacy and identity of the sender from other users, especially in electronic voting and electronic cash payment systems. A number of blind signcryption schemes are introduced over the years and some of them are proved to be insecure. In this Letter, the authors analysed a recently proposed blind signcryption scheme based on elliptic curves and proved it is insecure. Their analysis showed that the proposed scheme is unable to provide the claimed security attributes of message integrity, authentication, unforgeability, and signer non‐repudiation. After successful cryptanalysis, they introduced a modified version of this scheme to overcome the security flaws and weakness.